Broadening horizons: An exploration on the experiences of critical patients relatives - Agustina Díaz Sánchez; Nuria Díaz Sánchez (Fundación para el Desarrollo de la Enfermería, 2004)
The Purposes of this research were:1. To describe experiences from relatives of patients admitted in ICU and reanimation wards2. To analyze relationship between relatives and nurses working at ICU and reanimation wards3. To identify the demands of the relatives regarding nursing emotional support.Methodology: A qualitative study with an anthropological perspective was carried out. The fieldwork was carried out using two different techniques, participating observation and depth interviews. We paid special attention to the relationship between nurses and relatives, an essential skill for family support.Conclusions: An effective relationship between nurses and relatives is mandatory in order to implement an effective care giving. The support perceived by relatives is related to the relationship between them and the health professionals.